Tissue Engineered Bone Differentiated From Human Adipose Derived Stem Cells Inhibit Posterolateral Fusion in an Athymic Rat Model. Issue 8 (15th April 2018) - Saifi, Comron; Bernhard, Jonathan; Shillingford, Jamal N.; Petridis, Petros; Robinson, Samuel; Guo, X. Edward; Weidenbaum, Mark; Lehman, Ronald A.; An, Howard S.; Lenke, Lawrence G.; Vunjak-Novakovic, Gordana; Laratta, Joseph L.
Abstract : Study Design: Biological augmentation spinal arthrodesis trial in athymic rats. Objective: To assess the efficacy of tissue-engineered bone to promote L4-L5 intertransverse process fusion in an athymic rat model. Summary of Background Data: Each year in the United States, over 400, 000 spinal fusion surgeries are performed requiring bone graft. The current gold standard for posterolateral lumbar fusion is autogenous iliac crest bone graft (ICBG), but the harvesting of ICBG is associated with increased operative time and significant complications. This being the case, an alternative cost-effective bone graft source is needed. Methods: Bovine bone cores were sterilized and decellularized for scaffold production. Human adipose derived mesenchymal stem cells (ADSC) were obtained and verified by tridifferentiation testing and seeded onto dried scaffolds. The seeded cores were cultured for 5 weeks in culture medium designed to mimic endochondral ossification and produce hypertrophic chondrocytes. Single-level intertransverse process fusions were performed at the L4-L5 level of 31 athymic rats. Fifteen rats were implanted with the hypertrophic chondrocyte seeded scaffold and 16 had scaffold alone. Half of the study rats were sacrificed at 3 weeks and the other half at 6 weeks. Spinal fusion was assessed using 2D and 3D micro computed tomography (μCT) analysis and tissue histology. Results: At 3 weeks, none of the tissue engineered rats had partial or complete fusion, whereas 62.5% of the decellularized rats fused and another 12.5% had partial fusions ( P  = 0.013). At 6 weeks, none of the tissue engineered rats fused and 50% had partial fusions, whereas 87.5% of the decellularized rats fused ( P  = 0.002). Conclusion: Tissue engineered bone composed of hypertrophic chondrocytes inhibits posterolateral fusion in an athymic rat model and therefore does not represent a promising cost-effective bone graft substitute. Level of Evidence: N/A